Organic UV-Sensitive Phototransistors Based on Distriphenylamineethynylpyrene Derivatives with Ultra-High Detectivity Approaching 1018 - Tao, Jingwei (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.